PENGARUH UKURAN PARTIKEL TEPUNG KEDELAI DAN JUMLAH AIR PENGEKSTRAK TERHADAP HASIL DAN KUALITAS TAHU - , Arina Kurniati, S.Pt, Dr. Ir. M. Nur Cahyanto, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aims of this research are to investigate the effect of soy flour size and the ratio of the water extractor amounts on tofu yield and its quality, and to find out the amount of globulin protein fraction using different soy flour as a basic ingredient in tofu production. Experimental design was using Completely Randomized Factorial Design with two factors, that is soy flour size (40, 60, and 80 mesh) and the ratio of water extractors and soy flour (1:7, 1:9, and 1:11). The results showed that that using soy flour size from 60 mesh and soy flour and water extractors in the ratio of 1:9, the yield of wet tofu is about 242.92%, solids contents 49.52%, protein contents 58.35% (db), protein yield 71.90%, yield of 7S globulin 18.52%, yield of 11S globulin 30.70%, the amount of 7S globulin 31.73%, yield of 11S globulin 52.61%, tofu texture 7.30 N/mm 2 . Sensory test for color, taste and texture showed that panelists were accepted it. The tofu has a normal white color, tasteless, and sandy texture. Differences of soy flour size and the ratio between water extractors and soy flour affect tofu yield and its quality. The results showed that using soy flour size from 60 mesh and soy flour and water extractors in the ratio of 1:9 gives an optimal yield and better quality for the tofu products.